2018
DOI: 10.1098/rsos.172062
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional analyses provide new insight into the late-stage immune response of a diseased Caribbean coral

Abstract: Increasing global temperatures due to climate change have resulted in respective increases in the severity and frequency of epizootics around the globe. Corals in particular have faced rapid declines due to disease outbreaks. Understanding immune responses and associated potential life-history trade-offs is therefore a priority. In the autumn of 2011, a novel disease of octocorals of the genus Eunicea was first documented in the Florida Keys. Termed Eunicea Black Disease (EBD), the disease is easily identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 81 publications
(112 reference statements)
3
32
0
Order By: Relevance
“…Initial characterizations of cnidarian immune genes indicated that they possess key components of the major innate immune pathways including Toll/TLR pathway, complement C3, membrane attack complex/perforin domains, and other components of innate immunity once thought to have evolved much later (Miller et al, ; Nyholm & Graf, ; Putnam et al, ; Shinzato et al, ); yet, it was not known whether cnidarians used these immune pathways to mount a response against pathogens. A number of groups have since used RNA‐Seq data to produce some of the first profiles of anthozoan innate immunity (Anderson, Walz, Weil, Tonellato, & Smith, ; Burg, Prentis, Surm, & Pavasovic, ; Fuess, Mann, Jinks, Brinkhuis, & Mydlarz, ; Fuess, Pinzón, Weil, Grinshpon, & Mydlarz, ; Libro, Kaluziak, & Vollmer, ; Libro & Vollmer, ; Pinzón et al, ; Poole & Weis, ; Vidal‐Dupiol et al, ; Weiss et al, ). To date, at least nine studies have profiled the immune response of corals and their anthozoan relatives, and the data suggest that the immune response varies across anthozoans and/or immune exposures.…”
Section: Introductionmentioning
confidence: 99%
“…Initial characterizations of cnidarian immune genes indicated that they possess key components of the major innate immune pathways including Toll/TLR pathway, complement C3, membrane attack complex/perforin domains, and other components of innate immunity once thought to have evolved much later (Miller et al, ; Nyholm & Graf, ; Putnam et al, ; Shinzato et al, ); yet, it was not known whether cnidarians used these immune pathways to mount a response against pathogens. A number of groups have since used RNA‐Seq data to produce some of the first profiles of anthozoan innate immunity (Anderson, Walz, Weil, Tonellato, & Smith, ; Burg, Prentis, Surm, & Pavasovic, ; Fuess, Mann, Jinks, Brinkhuis, & Mydlarz, ; Fuess, Pinzón, Weil, Grinshpon, & Mydlarz, ; Libro, Kaluziak, & Vollmer, ; Libro & Vollmer, ; Pinzón et al, ; Poole & Weis, ; Vidal‐Dupiol et al, ; Weiss et al, ). To date, at least nine studies have profiled the immune response of corals and their anthozoan relatives, and the data suggest that the immune response varies across anthozoans and/or immune exposures.…”
Section: Introductionmentioning
confidence: 99%
“…Where O. faveolata is sensitive to disease and activates apoptotic responses to stress, P. astreoides is resistant to disease and activates autophagic responses to stress. Thus, the two stony coral represent intriguing systems to characterize the biochemical responses to stress (18).…”
Section: Discussionmentioning
confidence: 99%
“…Coral possess a rudimentary immune system that consists of innate immune pathways but no adaptive immune system (16). The invertebrate innate immune system is similar to that of vertebrates in utilizing physical and chemical barriers, cellular defenses, and humoral responses to pathogens (17), but in the relatively new field of ecological immunity, major knowledge gaps remain regarding the cellular defenses to disease (18). Although general response types have been outlined regarding receptor recognition, signaling pathways, and effector responses, such as metabolic changes, very few functional studies have been performed on the responses of coral to disease stressors (19).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell adhesion is important to maintaining the integrity of the tissue layer and within corals, evidence has been presented that factors, including heat stress and disease, can cause upregulation of genes involved in cell adhesion pathways [20,6063]. Interestingly, in previous coral disease studies, cell adhesion enrichment was present in corals that were showing signs of disease pathology and hypothesized to be due to the importance of apoptotic processes and phagocytosis of melanized particles and pathogens [20, 21]. Our findings show that cell adhesion is also important in corals not exhibiting visual signs of disease.…”
Section: Discussionmentioning
confidence: 99%